2006
DOI: 10.1248/bpb.29.2267
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Congestive Heart Failure on Mexiletine Pharmacokinetics in a Japanese Population

Abstract: 082 l/h/kg, mean؎S.D., pϽ0.05). Further, the CL/F ratio was 50% lower in group NYHA III-IV when compared with the Non-CHF group, and the CL/F ratio tended to change in inverse proportion to NYHA class. Conclusion: CHF status significantly affects mexiletine clearance. Therefore, dose adjustments and careful monitoring are likely required in CHF patients receiving mexiletine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 16 publications
0
12
0
2
Order By: Relevance
“…On the other hand, CYP2C9*3, CYP2C19*2, CYP2C19*3, CYP3A5*3, UGT2B7*2, UGT2B7*3, and the C3435T mutation of MDR1 did not affect the pharmacokinetics of R-and S-carvedilol in healthy Japanese. 2,6) Several pharmacokinetic studies have suggested that hepatic elimination of certain drugs via oxidative metabolism is impaired in patients with heart failure (HF) [7][8][9][10][11][12][13] ; that is, the CL/F value of prazosin after oral administration in HF patients was 46% of that in healthy subjects. 7) It was also reported that the CL/F value of aminopyrine after oral administration in HF patients in the aminopyrine breath test was 24% of that in control subjects.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, CYP2C9*3, CYP2C19*2, CYP2C19*3, CYP3A5*3, UGT2B7*2, UGT2B7*3, and the C3435T mutation of MDR1 did not affect the pharmacokinetics of R-and S-carvedilol in healthy Japanese. 2,6) Several pharmacokinetic studies have suggested that hepatic elimination of certain drugs via oxidative metabolism is impaired in patients with heart failure (HF) [7][8][9][10][11][12][13] ; that is, the CL/F value of prazosin after oral administration in HF patients was 46% of that in healthy subjects. 7) It was also reported that the CL/F value of aminopyrine after oral administration in HF patients in the aminopyrine breath test was 24% of that in control subjects.…”
mentioning
confidence: 99%
“…11,12) Recently, population pharmacokinetic analysis has revealed that the CL/F value of mexiletine, which is mainly metabolized by CYP1A2 and CYP2D6, is reduced significantly in HF patients as compared with non-HF patients. 13) However, it is still unclear whether the pharmacokinetics of R-and/or S-carvedilol is altered by HF. In the present study, therefore, we investigated the pharmacokinetics of R-and S-carvedilol in routinely treated Japanese patients with HF.…”
mentioning
confidence: 99%
“…By contrast, other studies did not report any significant differences in volume of distribution and elimination half‐life of lidocaine between HF patients and controls . The clearance of mexiletine was significantly reduced (−33%) in HF patients in one study , but not in another . No significant pharmacokinetic changes in HF patients were observed with procainamide in four studies, barring a significant reduction (between −17% and −49%) in clearance in two studies .…”
Section: Resultsmentioning
confidence: 72%
“…A total of 59 studies (49 on cardiovascular drugs) investigating 36 drugs (31 cardiovascular) were identified (Tables ). Twelve studies were published in the period 1970–1979 , 20 in the period 1980–1989 , 12 in the period 1990–1999 , 10 in the period 2000–2009 , and five in the period 2010–2018 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation